Preparation technology for preparing high-strength PP composite material based on waste plastic regeneration
By combining the synergistic effects of composite flame-retardant powder, reinforcing agent, and modified silicone resin, the problems of low flame-retardant efficiency, deteriorated mechanical properties, and poor aging resistance of recycled PP composite materials were solved, resulting in high-strength, high-temperature flame-retardant, and long-life PP composite materials.
Patent Information
- Application Number
- CN202511676663.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-17
- Publication Date
- 2025-12-16
AI Technical Summary
Existing technologies for recycled PP composite materials suffer from technical bottlenecks such as low flame retardancy efficiency, deterioration of mechanical properties, and poor aging resistance, making them difficult to apply in high-end fields.
By preparing composite flame-retardant powder, reinforcing agent and modified organosilicon resin synergistic effect, a phosphorus-nitrogen synergistic flame-retardant structure is formed, the interfacial bonding force is enhanced and a dense weather-resistant protective film is constructed, thereby improving the flame-retardant performance, mechanical properties and aging resistance of the material.
A high-strength, high-temperature resistant, flame-retardant, and long-life PP composite material has been developed, which significantly improves the limiting oxygen index, tensile strength, and impact toughness of the material, and slows down the rate of thermo-oxidative aging and environmental aging.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
TECHNICAL FIELD
[0001] The application relates to the technical field of regenerated PP composite materials, in particular to a preparation process for preparing high-strength PP composite materials based on waste plastic regeneration. BACKGROUND
[0002] Polypropylene is a kind of general-purpose plastic with wide application, and is in great demand in the fields of packaging, automobiles, household appliances and the like. The waste polypropylene plastic generated year by year is also increasing. The recycling and regeneration of waste polypropylene can not only alleviate the problem of resource shortage, but also reduce environmental pollution. Therefore, the preparation of PP composite materials based on waste plastic regeneration has become a research hotspot in the industry. However, the regenerated PP composite materials still face many technical bottlenecks in performance improvement, which limits their application in high-end fields.
[0003] In the prior art, the regenerated PP composite materials have technical bottlenecks in the improvement of three core performances of flame retardation, mechanical strengthening and aging resistance. In terms of flame retardation, halogen-based flame retardants have high efficiency but release toxic gases during combustion, which does not meet environmental protection requirements. Inorganic phosphorus-based flame retardants need to be added in a large amount to achieve the effect, which easily leads to the degradation of mechanical properties. Some phosphorus-nitrogen synergistic systems have poor compatibility between nitrogen source and phosphorus source, and are difficult to form stable cross-linked structures. At high temperatures, they cannot build a dense carbon layer, which not only lacks durability in flame retardation, but also is difficult to combine with the matrix, further exacerbating the decline in mechanical properties. In terms of mechanical strengthening, although inorganic fillers such as glass fibers and calcium carbonate can improve the strength, they have poor compatibility with the PP matrix and easily cause stress concentration, which leads to a large decrease in impact toughness. Ordinary organic reinforcing agents such as lignin fibers have good compatibility, but they are prone to aggregation during processing due to insufficient structural stability, and thus cannot fully play a role, and the mechanical properties are further deteriorated after the addition of flame retardants. In terms of aging resistance, the regenerated PP has poor weather resistance due to the degradation of molecular chains during processing, and most anti-aging agents only inhibit thermal-oxidative aging, and have limited blocking of ultraviolet light and moisture. Some organic silicon-based anti-aging agents can form a protective film, but they have poor compatibility with the matrix and the flame-retardant and reinforcing components, and are prone to migration and loss, which leads to the decay of aging resistance over time, and it is difficult to meet the long-term outdoor use requirements.
[0004] In summary, the traditional technology for preparing PP composite materials based on waste plastic regeneration cannot simultaneously solve the three core problems of low flame retardation efficiency, mechanical property deterioration and poor aging resistance. Therefore, it is necessary to develop a preparation process that can realize the synergistic effect of flame retardation, reinforcement and aging resistance, so as to promote the development of regenerated PP composite materials towards high performance and high added value. Therefore, a solution is proposed. SUMMARY
[0005] The purpose of the present application is to provide a preparation process for preparing high-strength PP composite materials based on waste plastic regeneration, so as to solve the technical defects mentioned above.
[0006] The application can be achieved by the following technical scheme: the preparation process of high-strength PP composite material prepared based on waste plastic regeneration, comprising the following steps:
[0007] S1, classify the waste plastic, then wash and crush the separated polypropylene plastic to obtain polypropylene fragments;
[0008] S2, the polypropylene fragments, maleic anhydride grafted polypropylene, composite flame-retardant powder, reinforcing agent, modified organic silicone resin and antioxidant 1010 are added into a banbury mixer, and are melt blended at 210-230 DEG C for 10-20 min, and the high-strength polypropylene composite material is obtained;
[0009] Further, the preparation method of the composite flame-retardant powder is:
[0010] Piperazine pyrophosphate, anhydrous ethanol and deionized water are added into a reaction kettle, stirred at 20-30 DEG C for 10-20 min, then melamine solution is added, stirred for 3-5 min, then phytic acid is added, and stirred for 3-5 min, then acetic acid solution is added dropwise to adjust the solution pH to 3-4, heated to 80-90 DEG C and reacted for 2 h, then treated, and the composite flame-retardant powder is obtained.
[0011] Reaction principle:
[0012]
[0013] First, piperazine pyrophosphate is fully dispersed in the mixed medium of anhydrous ethanol and deionized water, then melamine solution is added, the amino group in the molecular structure of melamine preferentially reacts with the phosphate group in the phytic acid molecule to form an intermediate containing nitrogen-phosphorus bond, then the remaining phosphate groups in the phytic acid molecule that do not participate in the previous reaction further react with the amino groups on the piperazine pyrophosphate molecule, and finally the target composite flame-retardant powder is obtained by washing, drying, grinding and sieving.
[0014] Further, the reinforcing agent is prepared by the following steps:
[0015] A1, lignin nanofiber is added into a reaction kettle containing anhydrous ethanol and deionized water, stirred at 20-30 DEG C for 5-10 min, then ultrasonic dispersed for 20-30 min, then acetic acid solution is added dropwise to adjust the solution pH to 4-5, then silane coupling agent is added, heated to 65-75 DEG C and stirred for 2-3 h, then treated to obtain coupling agent modified nanofiber;
[0016] A2. Add the coupling agent-modified nanofibers and dimethyl sulfoxide to the reactor, stir for 2-3 minutes, then add maleic anhydride and p-toluenesulfonic acid, stir at 65-75℃ for 2-3 hours, and then perform post-treatment to obtain the reinforcing agent.
[0017] Reaction principle:
[0018] The hydroxyl groups on the surface of lignin nanofibers are exposed in an aqueous ethanol solution. Under acidic conditions, the alkoxy groups of γ-methacryloxypropyltrimethoxysilane are hydrolyzed to generate silanol groups, which then undergo a condensation reaction with the hydroxyl groups on the surface of the lignin nanofibers to form Si-OC covalent bonds. This allows the coupling agent to be grafted onto the fiber surface, introducing unsaturated bonds of active organic functional groups. After treatment, coupling agent-modified nanofibers are obtained. Then, under the polar environment of dimethyl sulfoxide, p-toluenesulfonic acid is used as a proton catalyst to activate the anhydride groups of maleic anhydride. Under heating conditions, the maleic anhydride undergoes a ring-opening reaction with the active functional group hydroxyl group introduced by the coupling agent, forming an ester bond with the hydroxyl group and generating a carboxyl group at the other end. Finally, maleic anhydride is grafted onto the surface of the nanofibers, and after treatment, a reinforcing agent is obtained.
[0019] Furthermore, the modified organosilicon resin is prepared by the following steps:
[0020] B1. Add polytetrahydrofuran ether and isophorone diisocyanate to a reactor, then add dibutyltin dilaurate, heat to 70-90℃, and keep the reaction under argon atmosphere for 3-5 hours. After the system is cooled to 60℃, add 1,4-butanediol and continue the reaction for 3 hours. Discharge the material and cure it at 60℃ for 12 hours to obtain polyurethane.
[0021] B2. Add polydimethylsiloxane, pyridine and toluene to a reaction vessel, stir evenly under an argon atmosphere, add thionyl chloride, stir for 1-2 hours, and then perform post-treatment to obtain chlorinated polysiloxane.
[0022] B3. Dissolve potassium tert-butoxide in anhydrous ethylene glycol dimethyl ether, add polyurethane solution, stir in an ice bath for 1 hour under an argon atmosphere, then add chlorinated polysiloxane, stir in an ice bath for 2 hours, remove the ice bath, add saturated ammonium chloride, and perform post-treatment to obtain modified organosilicon resin.
[0023] Reaction principle:
[0024]
[0025] The terminal hydroxyl groups of polytetrahydrofuran ether undergo an addition reaction with the isocyanate groups of isophorone diisocyanate under the catalysis of dibutyltin dilaurate to form urethane bonds. Subsequently, the hydroxyl groups of 1,4-butanediol further react with the remaining isocyanate groups to extend the chain and form a polyurethane polymer. Then, the terminal hydroxyl groups of polydimethylsiloxane undergo a nucleophilic substitution reaction with thionyl chloride in the presence of pyridine, and the hydroxyl groups are replaced by chlorine atoms to form chlorinated polysiloxane. Finally, potassium tert-butoxide, as a strong base, abstracts the active hydrogen of the urethane bond in the polyurethane to generate a nucleophilic anion. This anion attacks the partially positively charged silicon atoms in the chlorinated polysiloxane, and a nucleophilic substitution reaction occurs to form a -Si-N- covalent bond, realizing the coupling of polyurethane and polysiloxane. After quenching with saturated ammonium chloride, desolventizing and drying, modified organosilicon resin is obtained.
[0026] Furthermore, in step S2, the ratio of the polypropylene fragments, maleic anhydride-grafted polypropylene, composite flame retardant powder, reinforcing agent, modified silicone resin, and antioxidant 1010 is 50-60g:3-5g:20-25g:20-25g:3-5g:0.1-0.3g.
[0027] Furthermore, the ratio of piperazine pyrophosphate, anhydrous ethanol, deionized water, melamine solution, and phytic acid is 40g:100mL:200mL:15mL:46-50g. The melamine solution is obtained by dissolving 1g of melamine in 30mL of pyridine. The acetic acid solution has a mass fraction of 10%. The post-treatment operation includes: after the reaction is completed, washing the product with deionized water at 60℃ 4-5 times, transferring it to a vacuum drying oven, drying it at 80℃ for 6h, grinding it, and passing it through a 100-mesh sieve to obtain composite flame retardant powder.
[0028] Further, in step A1, the ratio of lignin nanofibers, anhydrous ethanol, deionized water, and silane coupling agent is 0.8-1g:90mL:10mL:2g, and the silane coupling agent is γ-methacryloyloxypropyltrimethoxysilane. The post-treatment operation includes: after the reaction, centrifugation, washing with anhydrous ethanol 2-3 times, transferring to a vacuum drying oven, and drying at 60℃ for 12h to obtain coupling agent modified nanofibers; in step A2, the ratio of coupling agent modified nanofibers, dimethyl sulfoxide, maleic anhydride, and p-toluenesulfonic acid is 0.8-1g:80mL:2g:0.05g. The post-treatment operation includes: after the reaction, centrifugation, washing with anhydrous ethanol 2-3 times, transferring to a vacuum drying oven, and drying at 60℃ for 12h to obtain reinforcing agent.
[0029] Further, in step B1, the amount of polytetrahydrofuran ether added is 0.55 times the total molar amount of isocyanate groups in isophorone diisocyanate, and the ratio of isophorone diisocyanate, dibutyltin dilaurate, and 1,4-butanediol is 28-35g:0.05g:6-12g; in step B2, the ratio of polydimethylsiloxane, pyridine, toluene, and thionyl chloride is 10g:2-4mL:30-50mL:3-5mL. The post-treatment operation includes: after the reaction is completed, separation is performed, the upper liquid is filtered to remove the precipitate, the lower oily substance is washed with toluene 3-4 times, the obtained washing liquid is mixed with the upper liquid and the toluene and excess thionyl chloride are removed using a rotary evaporator, and then transferred to a vacuum drying oven to dry for 12 hours to obtain chlorinated polysiloxane.
[0030] Further, in step B3, the ratio of potassium tert-butoxide, anhydrous ethylene glycol dimethyl ether, polyurethane solution, chlorinated polysiloxane, and saturated ammonium chloride is 0.1-0.3g:30-50mL:1-2mL:1-3g:2-3g; the polyurethane solution is obtained by dissolving 6g of polyurethane in 30mL of anhydrous ethylene glycol dimethyl ether; the post-treatment operation includes: after the reaction is completed, the product is transferred to a rotary evaporator to remove the anhydrous ethylene glycol dimethyl ether, and then transferred to a vacuum drying oven to dry at 80℃ for 12h to obtain the modified organosilicon resin.
[0031] The present invention has the following beneficial effects:
[0032] 1. The composite flame-retardant powder of the present invention uses the hydroxymethylation product of 1,3,5-triaminobenzene and formaldehyde as a nitrogen source, combined with the pyrophosphate group of piperazine pyrophosphate and the polyphosphate group of phytic acid, to form a phosphorus-nitrogen synergistic flame-retardant structure through phosphoramide bonds. Nitrogen can promote the oxidative cross-linking of phosphorus and inhibit the release of combustible gases, while phosphorus can generate phosphoric acid flame-retardant substances at high temperature. Furthermore, the carboxyl groups on the surface of the anhydride-modified lignin nanofibers can interact with the amino and phosphoryl groups of the flame-retardant powder to help form a dense char layer, reducing heat and oxygen transfer. In addition, the polysiloxane segments in the modified organosilicon resin can form a siloxane heat-insulating protective layer at high temperature, further blocking the flame from contacting the substrate. Under the synergistic effect of the three, the PN flame-retardant system plays a core flame-suppressing role. The siloxane protective layer and the dense char layer construct a double heat-insulating barrier, significantly improving the limiting oxygen index of the composite polypropylene, reducing the heat release rate, and effectively inhibiting flame spread and dripping.
[0033] 2. This invention utilizes the high specific surface area and high strength of lignin nanofibers modified with anhydride. After modification with maleic anhydride, a large number of carboxyl groups are introduced onto the surface, which chemically bond with the ester groups of maleic anhydride-grafted polypropylene and the urethane bonds of the modified organosilicon resin. This strengthens the interfacial bonding between the fiber and the polypropylene matrix and reduces interfacial stress concentration. In addition, the modified organosilicon resin, through the synergy of polyurethane and polysiloxane segments, can improve the compatibility between the composite flame-retardant powder and the polypropylene matrix, and can also buffer external impacts through the flexibility of Si-O bonds. Then, the phosphoramide crosslinking structure of the composite flame-retardant powder can form secondary bonds with the carboxyl groups of the reinforcing agent and the silanol groups of the organosilicon resin to construct a three-dimensional network of "rigid reinforcement - flexible compatibility - crosslinking stability". The three work together to give the composite polypropylene excellent tensile strength and impact toughness, avoiding the mechanical property degradation caused by flame-retardant filling.
[0034] 3. The Si-O-Si bond energy in the modified organosilicon resin of this invention is much higher than that of the C-C bond. Its polysiloxane segments can form a dense weather-resistant protective film on the surface of the composite polypropylene, blocking aging factors such as oxygen, moisture and ultraviolet light from penetrating into the substrate. In addition, the phosphorus and nitrogen elements in the composite flame-retardant powder can capture free radicals generated during thermo-oxidative aging. Together with the antioxidant 1010 in the formula, they inhibit the thermo-oxidative degradation of polypropylene. Furthermore, the lignin nanofiber reinforcing agent modified with anhydride, after being modified with γ-methacryloyloxypropyltrimethoxysilane, is tightly bonded to the matrix interface, reducing the path for aging factors to penetrate from the interface gaps. At the same time, the aromatic ring structure of lignin itself also has a certain ability to resist ultraviolet aging. Under the synergistic effect of the three, the physical barrier of organosilicon, the free radical scavenging of flame-retardant powder and the interface stabilization of reinforcing agent form a multi-protection system, which significantly delays the thermo-oxidative aging and environmental aging rate of composite polypropylene and extends the service life of the material. Detailed Implementation
[0035] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0036] In this application, the maleic anhydride-grafted polypropylene is selected from Dongguan Taotao Plastic Raw Materials Co., Ltd., with an effective component content of 99.9% and a grade of 1020.
[0037] In this application, the lignin nanofibers are selected from Chengdu Junxinpeng New Material Technology Co., Ltd., and have a thickness of 25mm.
[0038] In this application, the polytetrahydrofuran ether is selected from Greenlink (Jining) Chemical Technology Co., Ltd., with a molecular weight of 1000, model number zhouyanai, and catalog number yaner71;
[0039] In this application, the polydimethylsiloxane is selected from Shandong Xinghai Chemical Co., Ltd., with CAS number 9006-65-9, model number 201, and viscosity of 100.
[0040] Example 1
[0041] This embodiment provides a preparation process for high-strength PP composite materials based on recycled waste plastics, including the following steps:
[0042] S1. Preparation of composite flame-retardant powder
[0043] Weigh out 1g of melamine and dissolve it in 30mL of pyridine to obtain a melamine solution;
[0044] Weigh out 40g of piperazine pyrophosphate, 100mL of anhydrous ethanol and 200mL of deionized water and add them to a reaction vessel. Stir at 20℃ for 10min. Then add 15mL of melamine solution and stir for 3min. Add 46g of phytic acid and stir for another 3min. Then add 10wt% acetic acid solution to adjust the pH of the solution to 3. Heat to 80℃ and keep the temperature for 2h. After the reaction is complete, wash the product 4 times with deionized water at 60℃, transfer it to a vacuum drying oven and dry at 80℃ for 6h. Grind and pass through a 100-mesh sieve to obtain composite flame retardant powder.
[0045] S2, Preparation of reinforcing agent
[0046] Weigh 8g of lignin nanofibers and add them to a reaction vessel containing 900mL of anhydrous ethanol and 100mL of deionized water. Stir at 20℃ for 5min, then sonicate for 20min. Then, add acetic acid solution dropwise to adjust the pH of the solution to 4. Next, add 20g of γ-methacryloyloxypropyltrimethoxysilane, heat to 65℃ and continue stirring for 2h. After the reaction is completed, centrifuge and wash twice with anhydrous ethanol. Transfer to a vacuum drying oven and dry at 60℃ for 12h to obtain coupling agent modified nanofibers.
[0047] Weigh out 8g of coupling agent-modified nanofibers and 800mL of dimethyl sulfoxide and add them to the reaction vessel. After stirring for 2 minutes, add 20g of maleic anhydride and 0.5g of p-toluenesulfonic acid. Stir at 65℃ for 2 hours. After the reaction is completed, centrifuge and wash twice with anhydrous ethanol. Transfer to a vacuum drying oven and dry at 60℃ for 12 hours to obtain the reinforcing agent.
[0048] S3. Preparation of modified organosilicon resin
[0049] Weigh out 28g of isophorone diisocyanate, calculate the amount of polytetrahydrofuran ether to be added based on 0.55 times the total molar amount of isocyanate groups in isophorone diisocyanate, and add it to the reactor. Then add 0.05g of dibutyltin dilaurate, heat to 70℃, and keep the reaction at 70℃ for 3 hours. After the system is cooled to 60℃, add 6g of 1,4-butanediol and continue the reaction for 3 hours. Discharge the material and cure it at 60℃ for 12 hours to obtain polyurethane.
[0050] Weigh out 20g of polydimethylsiloxane, 4mL of pyridine and 60mL of toluene and add them to the reaction vessel. Stir well under an argon atmosphere, then add 6mL of thionyl chloride and stir for 1h. After the reaction is complete, separate the liquid and filter the upper liquid to remove the precipitate. Wash the lower oily substance three times with toluene. Mix the washing liquid with the upper liquid and use a rotary evaporator to remove toluene and excess thionyl chloride. Then transfer it to a vacuum drying oven and dry for 12h to obtain chlorinated polysiloxane.
[0051] Weigh out 60g of polyurethane and dissolve it in 300mL of anhydrous ethylene glycol dimethyl ether to obtain a polyurethane solution.
[0052] Weigh out 1g of potassium tert-butoxide and dissolve it in 300mL of anhydrous ethylene glycol dimethyl ether. Add 10mL of polyurethane solution to the solution and stir in an ice bath for 1h under an argon atmosphere. Then add 10g of chlorinated polysiloxane and stir in an ice bath for 2h. Remove the ice bath and finally add 20g of saturated ammonium chloride. After the reaction is complete, transfer the product to a rotary evaporator to remove the anhydrous ethylene glycol dimethyl ether, and then transfer it to a vacuum drying oven to dry at 80℃ for 12h to obtain the modified organosilicon resin.
[0053] S4. Preparation of polypropylene fragments
[0054] Waste plastics are sorted, and then the separated polypropylene plastics are washed and crushed to obtain polypropylene fragments.
[0055] S5. Preparation of polypropylene composite materials
[0056] Weigh out 500g of polypropylene fragments, 30g of maleic anhydride-grafted polypropylene, 200g of composite flame retardant powder, 200g of reinforcing agent, 30g of modified organosilicon resin and 1g of antioxidant 1010 and add them together into a mixer. Melt and blend at 210℃ for 10 minutes, then discharge to obtain a high-strength polypropylene composite material.
[0057] Example 2
[0058] This embodiment provides a preparation process for high-strength PP composite materials based on recycled waste plastics, including the following steps:
[0059] S1. Preparation of composite flame-retardant powder
[0060] Weigh out 1g of melamine and dissolve it in 30mL of pyridine to obtain a melamine solution;
[0061] Weigh out 40g of piperazine pyrophosphate, 100mL of anhydrous ethanol and 200mL of deionized water and add them to a reaction vessel. Stir at 25℃ for 15min. Then add 15mL of melamine solution and stir for 4min. Add 48g of phytic acid and stir for another 4min. Then add 10wt% acetic acid solution to adjust the pH of the solution to 3.5. Heat to 85℃ and keep the temperature for 2h. After the reaction is complete, wash the product 4 times with deionized water at 60℃, transfer it to a vacuum drying oven and dry at 80℃ for 6h. Grind and pass through a 100-mesh sieve to obtain composite flame retardant powder.
[0062] S2, Preparation of reinforcing agent
[0063] Weigh 9g of lignin nanofibers and add them to a reaction vessel containing 900mL of anhydrous ethanol and 100mL of deionized water. Stir at 25℃ for 8min, then sonicate for 25min. Add acetic acid solution dropwise to adjust the pH of the solution to 4.5. Then add 20g of γ-methacryloyloxypropyltrimethoxysilane, heat to 70℃ and continue stirring for 2.5h. After the reaction is complete, centrifuge and wash twice with anhydrous ethanol. Transfer to a vacuum drying oven and dry at 60℃ for 12h to obtain coupling agent modified nanofibers.
[0064] Weigh out 9g of coupling agent-modified nanofibers and 800mL of dimethyl sulfoxide and add them to the reaction vessel. After stirring for 2 minutes, add 20g of maleic anhydride and 0.5g of p-toluenesulfonic acid. Stir at 70℃ for 2.5h. After the reaction is completed, centrifuge and wash twice with anhydrous ethanol. Transfer to a vacuum drying oven and dry at 60℃ for 12h to obtain the reinforcing agent.
[0065] S3. Preparation of modified organosilicon resin
[0066] Weigh out 31g of isophorone diisocyanate, calculate the amount of polytetrahydrofuran ether to be added based on 0.55 times the total molar amount of isocyanate groups in isophorone diisocyanate, and add it to the reactor. Then add 0.05g of dibutyltin dilaurate, heat to 80℃, and keep the reaction at 80℃ for 4 hours. After the system is cooled to 60℃, add 9g of 1,4-butanediol and continue the reaction for 3 hours. Discharge the material and cure it at 60℃ for 12 hours to obtain polyurethane.
[0067] Weigh 20g of polydimethylsiloxane, 6mL of pyridine and 80mL of toluene and add them to the reaction vessel. Stir well under an argon atmosphere, then add 8mL of thionyl chloride and stir for 1.5h. After the reaction is complete, separate the liquid and filter the upper liquid to remove the precipitate. Wash the lower oily substance three times with toluene. Mix the washing liquid with the upper liquid and use a rotary evaporator to remove toluene and excess thionyl chloride. Then transfer it to a vacuum drying oven and dry for 12h to obtain chlorinated polysiloxane.
[0068] Weigh out 60g of polyurethane and dissolve it in 300mL of anhydrous ethylene glycol dimethyl ether to obtain a polyurethane solution.
[0069] Weigh out 2g of potassium tert-butoxide and dissolve it in 400mL of anhydrous ethylene glycol dimethyl ether. Add 15mL of polyurethane solution to the solution and stir in an ice bath for 1h under an argon atmosphere. Then add 20g of chlorinated polysiloxane and stir in an ice bath for 2h. Remove the ice bath and add 25g of saturated ammonium chloride. After the reaction is complete, transfer the product to a rotary evaporator to remove the anhydrous ethylene glycol dimethyl ether and then transfer it to a vacuum drying oven to dry at 80℃ for 12h to obtain the modified organosilicon resin.
[0070] S4. Preparation of polypropylene fragments
[0071] Waste plastics are sorted, and then the separated polypropylene plastics are washed and crushed to obtain polypropylene fragments.
[0072] S5. Preparation of polypropylene composite materials
[0073] Weigh out 550g of polypropylene fragments, 40g of maleic anhydride-grafted polypropylene, 220g of composite flame retardant powder, 220g of reinforcing agent, 40g of modified organosilicon resin and 2g of antioxidant 1010 and add them together into a mixer. Melt and blend at 220℃ for 15 minutes, then discharge to obtain a high-strength polypropylene composite material.
[0074] Example 3
[0075] This embodiment provides a preparation process for high-strength PP composite materials based on recycled waste plastics, including the following steps:
[0076] S1. Preparation of composite flame-retardant powder
[0077] Weigh out 1g of melamine and dissolve it in 30mL of pyridine to obtain a melamine solution;
[0078] Weigh out 40g of piperazine pyrophosphate, 100mL of anhydrous ethanol and 200mL of deionized water and add them to a reaction vessel. Stir at 30℃ for 20min. Then add 15mL of melamine solution and stir for 5min. Add 50g of phytic acid and stir for another 5min. Then add 10wt% acetic acid solution to adjust the pH of the solution to 4. Heat to 90℃ and keep the temperature for 2h. After the reaction is complete, wash the product 5 times with deionized water at 60℃, transfer it to a vacuum drying oven and dry at 80℃ for 6h. Grind and pass through a 100-mesh sieve to obtain composite flame retardant powder.
[0079] S2, Preparation of reinforcing agent
[0080] Weigh 10g of lignin nanofibers and add them to a reaction vessel containing 900mL of anhydrous ethanol and 100mL of deionized water. Stir at 30℃ for 10min, then sonicate for 30min. Add acetic acid solution dropwise to adjust the pH of the solution to 5. Then add 20g of γ-methacryloyloxypropyltrimethoxysilane, heat to 75℃ and continue stirring for 3h. After the reaction is complete, centrifuge and wash three times with anhydrous ethanol. Transfer to a vacuum drying oven and dry at 60℃ for 12h to obtain coupling agent modified nanofibers.
[0081] Weigh out 10g of coupling agent-modified nanofibers and 800mL of dimethyl sulfoxide and add them to the reaction vessel. After stirring for 3 minutes, add 20g of maleic anhydride and 0.5g of p-toluenesulfonic acid. Stir at 75℃ for 3 hours. After the reaction is complete, centrifuge and wash three times with anhydrous ethanol. Transfer to a vacuum drying oven and dry at 60℃ for 12 hours to obtain the reinforcing agent.
[0082] S3. Preparation of modified organosilicon resin
[0083] Weigh out 35g of isophorone diisocyanate, calculate the amount of polytetrahydrofuran ether to be added based on 0.55 times the total molar amount of isocyanate groups in isophorone diisocyanate, and add them together to the reactor. Then add 0.05g of dibutyltin dilaurate, heat to 90℃, and keep the reaction at 90℃ for 5 hours. After the system is cooled to 60℃, add 12g of 1,4-butanediol and continue the reaction for 3 hours. Discharge the material and cure it at 60℃ for 12 hours to obtain polyurethane.
[0084] Weigh out 20g of polydimethylsiloxane, 8mL of pyridine and 100mL of toluene and add them to the reaction vessel. Stir well under an argon atmosphere, then add 10mL of thionyl chloride and stir for 2 hours. After the reaction is complete, separate the liquid and filter the upper liquid to remove the precipitate. Wash the lower oily substance with toluene 4 times. Mix the washing liquid with the upper liquid and use a rotary evaporator to remove toluene and excess thionyl chloride. Then transfer it to a vacuum drying oven and dry for 12 hours to obtain chlorinated polysiloxane.
[0085] Weigh out 60g of polyurethane and dissolve it in 300mL of anhydrous ethylene glycol dimethyl ether to obtain a polyurethane solution.
[0086] Weigh out 3g of potassium tert-butoxide and dissolve it in 500mL of anhydrous ethylene glycol dimethyl ether. Add 20mL of polyurethane solution to the solution and stir in an ice bath for 1h under an argon atmosphere. Then add 30g of chlorinated polysiloxane and stir in an ice bath for 2h. Remove the ice bath and add 30g of saturated ammonium chloride. After the reaction is complete, transfer the product to a rotary evaporator to remove the anhydrous ethylene glycol dimethyl ether and then transfer it to a vacuum drying oven to dry at 80℃ for 12h to obtain the modified organosilicon resin.
[0087] S4. Preparation of polypropylene fragments
[0088] Waste plastics are sorted, and then the separated polypropylene plastics are washed and crushed to obtain polypropylene fragments.
[0089] S5. Preparation of polypropylene composite materials
[0090] Weigh out 600g of polypropylene fragments, 50g of maleic anhydride-grafted polypropylene, 250g of composite flame retardant powder, 250g of reinforcing agent, 50g of modified silicone resin and 3g of antioxidant 1010 and add them to a mixer. Melt and blend at 230℃ for 20 minutes, then discharge to obtain a high-strength polypropylene composite material.
[0091] Comparative Example 1
[0092] The difference between this comparative example and Example 3 is that step S1 is omitted and composite flame retardant powder is not added in step S5.
[0093] Comparative Example 2
[0094] The difference between this comparative example and Example 3 is that step S2 is omitted and no reinforcing agent is added in step S5.
[0095] Comparative Example 3
[0096] The difference between this comparative example and Example 3 is that step S3 is omitted and modified organosilicon resin is not added in step S5.
[0097] Performance testing:
[0098] The vertical flammability ratings of the polypropylene composites prepared in Examples 1-3 and Comparative Examples 1-3 were determined according to standard GB / T 2408-2021 "Determination of flammability of plastics - Horizontal and Vertical Methods".
[0099] The oxygen index of the polypropylene composites prepared in Examples 1-3 and Comparative Examples 1-3 was determined according to the standard GB / T 2406.2-2009 "Determination of Combustion Behavior by Oxygen Index Method for Plastics - Part 2: Room Temperature Test".
[0100] The tensile strength of the polypropylene composites prepared in Examples 1-3 and Comparative Examples 1-3 was determined in accordance with the standard GB / T 1040.1-2018 "Determination of tensile properties of plastics - Part 1: General".
[0101] The tensile strength of the polypropylene composites prepared in Examples 1-3 and Comparative Examples 1-3 was determined according to standard GB / T 1040.1-2018 "Determination of tensile properties of plastics - Part 1: General". The specific test results are shown in Table 1 below:
[0102] Table 1 - Basic Performance Test Data of the Samples
[0103]
[0104] The polypropylene composite materials prepared in Examples 1-3 and Comparative Examples 1-3 were aged according to standard GB / T 3681.2-2021 "Plastics Solar Radiation Exposure Test Methods Part 2: Direct Natural Climate Aging and Climate Aging after Exposure to Window Glass". The vertical flammability, oxygen index, tensile strength, and notched super strength of the cantilever beam were then measured. Specific test results are shown in Table 2 below.
[0105] Table 2 - Performance test data of the samples after oxidation
[0106]
[0107] Data Analysis:
[0108] Comparative analysis of the data in Table 1 above shows that the high-strength polypropylene composite material prepared by this invention has a vertical flammability rating of V-0, an oxygen index of 29.2%, a tensile strength of 46.5 MPa, and a cantilever beam notched impact strength of 5.1 kJ / m². 2 ;
[0109] In the composite materials of Examples 1-3 in Table 1, the composite flame-retardant powder constructs a phosphorus-nitrogen synergistic flame-retardant structure, which can promote the oxidative crosslinking of phosphorus, inhibit the release of combustible gases, and assist in the formation of a dense char layer. The polysiloxane segments of the modified organosilicon resin can also form a siloxane thermal insulation protective layer. The two, together with the reinforcing agent, synergistically construct a double thermal insulation barrier. Therefore, their vertical burning ratings all reach V-0, and their oxygen index reaches 28.4-29.2%, which is much higher than that of Comparative Example 1 without composite flame-retardant powder. At the same time, the anhydride-modified lignin nanofiber reinforcing agent forms chemical bonds with the matrix through carboxyl groups, reducing interfacial stress concentration. The modified organosilicon resin can also improve compatibility and buffer impact. The three construct a three-dimensional network of "rigid reinforcement - flexible compatibility - crosslinking stability". Therefore, the tensile strength of the examples is 45.7-46.5 MPa, and the notched impact strength of the cantilever beam is 4.8-5.1 kJ / m. 2 It is significantly superior to Comparative Example 2 without reinforcing agent and Comparative Example 3 without modified silicone resin;
[0110] In the composite materials of Examples 1-3 in Table 2, the modified organosilicon resin has high Si-O-Si bond energy, which can form a dense, weather-resistant protective film to block aging factors. The phosphorus and nitrogen elements in the composite flame-retardant powder can capture thermo-oxidative aging free radicals. Combined with antioxidant 1010, it inhibits thermo-oxidative degradation. Furthermore, the reinforcing agent and matrix interface are tightly bonded, reducing the penetration path of aging factors. Multiple protections delay aging, so after aging, it still maintains a V-0 flammability rating, an oxygen index of 23.9-25.1%, a tensile strength of 38.4-39.9 MPa, and an impact strength of 4.0-4.1 kJ / m. 2 The retention rate was high; however, Comparative Example 1 lacked composite flame retardant powder and could not effectively capture free radicals, Comparative Example 2 lacked reinforcing agent and had interfacial gaps that allowed aging factors to easily penetrate, and Comparative Example 3 lacked modified organosilicon resin and lost physical barrier. Therefore, the vertical burning rating of all three decreased to V-2 after aging, and their oxygen index, tensile strength and impact strength were far lower than those of the examples.
[0111] The preferred embodiments of the present invention disclosed above are merely illustrative of the invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the invention to specific implementations. Clearly, many modifications and variations can be made based on the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the invention, thereby enabling those skilled in the art to better understand and utilize the invention. The invention is limited only by the claims and their full scope and equivalents.
Claims
1. A preparation process for high-strength PP composite materials based on recycled waste plastics, characterized in that, Includes the following steps: S1. Sort the waste plastics, then wash and crush the separated polypropylene plastics to obtain polypropylene fragments; S2. Add polypropylene fragments, maleic anhydride-grafted polypropylene, composite flame retardant powder, reinforcing agent, modified organosilicon resin and antioxidant 1010 together into a mixer, melt-blend at 210-230℃ for 10-20 minutes, and discharge to obtain a high-strength polypropylene composite material. The preparation method of the composite flame retardant powder is as follows: piperazine pyrophosphate, anhydrous ethanol and deionized water are added to a reaction vessel and stirred at 20-30℃ for 10-20 min. Then, melamine solution is added and stirred for 3-5 min. Phytic acid is added and stirred for another 3-5 min. Finally, acetic acid solution is added dropwise to adjust the pH of the solution to 3-4. The temperature is raised to 80-90℃ and kept at that temperature for 2 h. After post-treatment, the composite flame retardant powder is obtained. The reinforcing agent is prepared by the following steps: A1. Add lignin nanofibers to a reaction vessel containing anhydrous ethanol and deionized water. Stir at 20-30℃ for 5-10 min, then ultrasonically disperse for 20-30 min. Then, add acetic acid solution dropwise to adjust the pH of the solution to 4-5. Next, add silane coupling agent, heat to 65-75℃ and continue stirring for 2-3 h. After post-treatment, obtain coupling agent modified nanofibers. A2. Add the coupling agent-modified nanofibers and dimethyl sulfoxide to the reaction vessel, stir for 2-3 minutes, then add maleic anhydride and p-toluenesulfonic acid, stir at 65-75℃ for 2-3 hours, and then perform post-treatment to obtain the reinforcing agent. The modified organosilicon resin is prepared by the following steps: B1. Add polytetrahydrofuran ether and isophorone diisocyanate to a reactor, then add dibutyltin dilaurate, heat to 70-90℃, and keep the reaction under argon atmosphere for 3-5 hours. After the system is cooled to 60℃, add 1,4-butanediol and continue the reaction for 3 hours. Discharge the material and cure it at 60℃ for 12 hours to obtain polyurethane. B2. Add polydimethylsiloxane, pyridine and toluene to a reaction vessel, stir evenly under an argon atmosphere, add thionyl chloride, stir for 1-2 hours, and then perform post-treatment to obtain chlorinated polysiloxane. B3. Dissolve potassium tert-butoxide in anhydrous ethylene glycol dimethyl ether, add polyurethane solution, stir in an ice bath for 1 hour under an argon atmosphere, then add chlorinated polysiloxane, stir in an ice bath for 2 hours, remove the ice bath, add saturated ammonium chloride, and perform post-treatment to obtain modified organosilicon resin.
2. The preparation process for high-strength PP composite materials based on recycled waste plastics according to claim 1, characterized in that, In step S2, the ratio of polypropylene fragments, maleic anhydride-grafted polypropylene, composite flame retardant powder, reinforcing agent, modified silicone resin and antioxidant 1010 is 50-60g:3-5g:20-25g:20-25g:3-5g:0.1-0.3g.
3. The preparation process for high-strength PP composite materials based on recycled waste plastics according to claim 1, characterized in that, The ratio of piperazine pyrophosphate, anhydrous ethanol, deionized water, melamine solution, and phytic acid is 40g:100mL:200mL:15mL:46-50g. The melamine solution is obtained by dissolving 1g of melamine in 30mL of pyridine. The acetic acid solution has a mass fraction of 10%. The post-treatment operation includes: after the reaction is completed, washing the product with deionized water at 60℃ 4-5 times, transferring it to a vacuum drying oven, drying it at 80℃ for 6h, grinding it, and passing it through a 100-mesh sieve to obtain composite flame retardant powder.
4. The preparation process for high-strength PP composite materials based on recycled waste plastics according to claim 1, characterized in that, In step A1, the ratio of lignin nanofibers, anhydrous ethanol, deionized water, and silane coupling agent is 0.8-1g:90mL:10mL:2g, and the silane coupling agent is γ-methacryloyloxypropyltrimethoxysilane. The post-treatment operation includes: after the reaction, centrifugation, washing with anhydrous ethanol 2-3 times, transferring to a vacuum drying oven, and drying at 60℃ for 12h to obtain coupling agent modified nanofibers. In step A2, the ratio of coupling agent modified nanofibers, dimethyl sulfoxide, maleic anhydride, and p-toluenesulfonic acid is 0.8-1g:80mL:2g:0.05g. The post-treatment operation includes: after the reaction, centrifugation, washing with anhydrous ethanol 2-3 times, transferring to a vacuum drying oven, and drying at 60℃ for 12h to obtain reinforcing agent.
5. The preparation process for high-strength PP composite materials based on recycled waste plastics according to claim 1, characterized in that, In step B1, the amount of polytetrahydrofuran ether added is 0.55 times the total molar amount of isocyanate groups in isophorone diisocyanate, and the ratio of isophorone diisocyanate, dibutyltin dilaurate, and 1,4-butanediol is 28-35g:0.05g:6-12g; in step B2, the ratio of polydimethylsiloxane, pyridine, toluene, and thionyl chloride is 10g:2-4mL:30-50mL:3-5mL. The post-treatment operation includes: after the reaction is completed, separation is performed, the upper liquid is filtered to remove the precipitate, the lower oily substance is washed with toluene 3-4 times, the resulting washing liquid is mixed with the upper liquid and the toluene and excess thionyl chloride are removed using a rotary evaporator, and then transferred to a vacuum drying oven to dry for 12 hours to obtain chlorinated polysiloxane.
6. The preparation process for high-strength PP composite materials based on recycled waste plastics according to claim 1, characterized in that, In step B3, the ratio of potassium tert-butoxide, anhydrous ethylene glycol dimethyl ether, polyurethane solution, chlorinated polysiloxane and saturated ammonium chloride is 0.1-0.3g:30-50mL:1-2mL:1-3g:2-3g; The polyurethane solution was obtained by dissolving 6g of polyurethane in 30mL of anhydrous ethylene glycol dimethyl ether; the post-treatment operation included: after the reaction was completed, the product was transferred to a rotary evaporator to remove the anhydrous ethylene glycol dimethyl ether, and then transferred to a vacuum drying oven to dry at 80°C for 12h to obtain the modified organosilicon resin.
Citation Information
Patent Citations
Phytic acid supramolecular flame retardant, preparation method and application
CN114773615A
Recycled fireproof flame-retardant plastic formula and preparation method thereof
CN115850864A
Method for modifying lignin and modified lignin using the method and composition material containing the modified lignin
KR101548466B1
Cited By
Moisture-proof flame-retardant corrugated board and preparation process thereof
CN121593368A
Moisture-proof and flame-retardant corrugated paperboard and preparation process thereof
CN121593368B
